A rare case of disseminated Sporothrix schenckii with bone marrow involvement in a patient with idiopathic CD4 lymphocytopenia. (2017) - Yagnik, Kruti J.; Skelton, William Paul; Olson, Angela; Trillo, Cesar A.; Lascano, Jorge
Abstract: Sporothrix schenckii is a pathogen with a predilection for dissemination in immunocompromised individuals, often with HIV. We report a case of disseminated sporotrichosis in an unfortunate 25 year old male (without HIV) who was originally treated for presumed pneumonia. The patient continued to worsen clinically and further work-up eventually revealed Sporothrix schenckii species with involvement of multiple organs including the skin, heart, lungs and bone marrow. Despite treatment with multiple antibacterials and antifungals, he ultimately passed away. This case illustrates the aggressive nature of this disease along with the importance of early/proper diagnosis and treatment.